Characteristics and indication of hydrocarbon-generating organisms in sub-salt Majiagou Formation of well T112, central and eastern Ordos Basin - Yinuo ZHANG; Dongdong ZHANG; Liubin WEI; Wenhui LIU; Pingping SHI; Xiaofeng WANG; Qian ZHANG; Yining LI; Zhicheng JIN (Shiyou shiyan dizhi)
In recent years, breakthroughs in natural gas exploration have been continuously achieved in the Ordovician Majiagou Formation of the central and eastern Ordos Basin, with geochemical characteristics of self-generation and self-storage. However, there are still controversies surrounding the evaluation of carbonate hydrocarbon source rocks in the Majiagou Formation, characterized by low organic matter abundance and high thermal evolution. Research on hydrocarbon-generating organisms can provide new perspectives and methodologies for assessing the hydrocarbon potential and source environments of these rocks. The study analyzed the core samples from the Majiagou Formation of the well T112 in the Ordos Basin using optical microscopy, scanning electron microscopy, and geochemical analyses. The results revealed various types of hydrocarbon-generating organisms with vertical distribution differences. These organisms primarily included planktonic algae, benthic algae, animal organic debris, and mineral-bituminous groundmass. Different assemblages of these organisms were observed across various members of the Majiagou Formation. The fifth member (Ma 5 member) contained more planktonic algae, the fourth member (Ma 4 member) was dominated by benthic algae, and the third member (Ma 3 member) predominantly contained mineral bituminous groundmass. Geochemical data indicated higher total organic carbon (TOC) content in the Ma 3 and Ma 5 members, with minimal variations in organic carbon isotope compositions. Carbon and oxygen isotopes in the Ma 3 member are generally lighter. Comprehensive analysis suggested that the sedimentary environments in the Ma 3 and Ma 5 members were favorable for the development of hydrocarbon-generating organisms. The high TOC values in these members were associated with planktonic algae, while saline environment, terrigenous inputs, and restricted marine sedimentary facies were the primary controlling factors on phytoplankton development. Moreover, negative drifts in inorganic carbon isotopes indicated that large-scale hydrocarbon generation events have occurred in the Majiagou Formation, suggesting that its carbonate rock sequences might be an effective hydrocarbon source for oil and gas accumulation.